EFFECT OF VITAMIN C ON mRNA EXPRESSION OF BMPs DURING FRACTURE HEALING IN THE FEMUR CALLUS OF SPRAGUE-DAWLEY FEMALE RATS - ANBARASI, G.; KUMAR, K. SENTHIL; NARMADHA, P.; SRINIVASAN, N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Fracture reparation is a complex physiological process. During fracture healing no scar is left but a new bone tissue is created. In addition to mechanical stabilization, inflammatory cytokines, growth factors, vitamins and trace elements are needed for better and faster fracture healing. Though vitamin C and BMPs are implicated in fracture healing, the interactions between them are not known. Objective: The present study was performed to delineate the role of vitamin C in the regulation of BMPs mRNA expression in the callus femur. Methods: In this regard, unilateral fracture was induced in the femur of Sprague-Dawley female rats and treated with vitamin C (200 mg/kbwt/ip on alternate days for 21 days). Results: The mRNA expression of BMP 2, BMP 4 and BMP 6 was assessed by RT-PCR from the harvested fracture callus on days 7, 14 and 21. The mRNA expression of BMP-2 and BMP-6 was significantly increased in the callus femur on all points of study. However, BMP-4 mRNA was increased on days 7 and 14 only. Conclusion: Thus the results clearly indicated that vitamin C directs the fracture healing by up regulating the expression of BMPs during 7, 14 and 21 days. Future studies are essential to quantify the levels of these BMPs. Thus it is concluded that vitamin C places a pivotal role in increased expression of BMPs during fracture healing.